The Airbus A320 family fan cowl door safety modification: a human factors scenario analysis - Kourousis, Kyriakos I.; Chatzi, Anna V.; Giannopoulos, Ioannis K. (Emerald, 2018)
Purpose The Airbus A320 family engine fan cowl doors (FCDs) safety issue is known to the industry for almost 18 years; however, it has not been addressed adequately by the aircraft manufacturer and the various operators and regulating authorities. The purpose of this paper is to examine in a systematic way the possible operational and safety implications of a new modification on the engine FCDs. Design/methodology/approach An array of error-prone scenarios is presented and analysed under the prism of human factors in a non-exhaustive qualitative scenario analysis. Findings All examined scenarios are considered more or less probable. A number of accident prevention solutions are proposed for each of the scenario examined, in view of the acceptance and implementation of this modification by operators. Research limitations/implications As these scenarios are neither exhaustive nor have been tested/validated in actual aircraft maintenance practice, the further analysis is necessary. A substantial follow-up survey should take place, which should include a wider array of scenarios. This would allow obtaining the necessary data for a quantitative (statistical) analysis. Practical implications This case study identifies issues in relation to this modification, introduced by Airbus and the European Aviation Safety Agency (EASA), which may prove problematic from the point of view of safety effectiveness and disruption of operations. Originality/value This case study examines a long-standing aviation safety issue and the implications of a solution proposed by the aircraft manufacturer and adopted by EASA. This can be useful in increasing the awareness around these issues and highlight the importance of a human-centric and scenario-based design of engineering modifications towards minimising error in aircraft technical operations.
Keywords: Human factors; Safety; Airworthiness; Accident prevention; Aviation maintenance